2019
DOI: 10.9734/jemt/2019/v22i630110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Macroeconomic Variables on Stock Market Performance in Nigeria

Abstract: This paper aims at examining the effect of macroeconomic variables on stock market performance in Nigeria using annual time series data spanning 1981 to 2016.The data were obtained from Central Bank of Nigeria (CBN) Statistical Bulletin. Four macroeconomic variables, namely: money supply, interest rate, exchange rate and inflation rate were used as independent variables, while market capitalisation (proxy for stock market performance) was employed as the dependent variable. The results of Augmented Dickey-Full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 7 publications
3
17
1
2
Order By: Relevance
“…Reading market trends and making a wise decision by investors could be relied on either technical analysis or fundamental analysis or perhaps it's based on both [2]. Looking over the movement of specific stock historical prices and predicting its future trend is called technical analysis.…”
Section: Empirical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reading market trends and making a wise decision by investors could be relied on either technical analysis or fundamental analysis or perhaps it's based on both [2]. Looking over the movement of specific stock historical prices and predicting its future trend is called technical analysis.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…The study revealed that both interest rate and money supply had a significant impact on stock prices. Meanwhile, [2] illustrated that money supply and interest rate are the factors due to their significant influences on Nigeria's stock market between 1981 and 2016.…”
Section: Article Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that economic development is significantly influenced by GDP, inflation rate, exchange rate and stock prices. John (2019) carried out a study in Nigeria to examine stock market performance and effects of money supply, annual interest rate and inflation. He used annual data series spanning 1981 to 2016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Etale and Eze found significant positive impact of money supply and exchange rate and negative effect of interest rate and inflation ration on stock market performance. Stock market performance is significantly influenced by macroeconomic variables and money supply has significant positive impact and interest rate has significant negative impact whereas exchange rate and inflation have no effect on stock market performance (John, 2019).…”
Section: Introductionmentioning
confidence: 99%